Editorial - Fredericks, Bronwyn; Nakata, Martin; Barney, Katelyn (The Australian Journal of Indigenous Education, 2023)
We are very pleased to bring you Volume 52 Issue 1 of The Australian Journal of Indigenous Education. This year the journal celebrates its 50th anniversary! The journal has a long history beginning in 1973 as The Aboriginal Child at School. From its infancy, The Aboriginal Child at School played an important role in responding to the challenging and urgent tasks facing teachers of Aboriginal and Torres Strait Islander children through the publication of practical information and support and fostering research and publication of findings in relevant areas. In 1996 The Aboriginal Child at School was transformed into The Australian Journal of Indigenous Education and reduced to two issues per year. The decision was made to change the title as a result of feedback from educators involved in Aboriginal and Torres Strait Islander education and also to reflect a broadening of the content of the journal to include international perspectives. In 2003, coinciding with the 30th anniversary of the journal, the decision was taken to relaunch AJIE as a peer reviewed research journal. From 2012 to 2021 AJIE was published by Cambridge University Press and in 2022 AJIE began an exciting new future as a fully open access scholarly publication. This year we also welcome a new Editorial Board and we thank them for their service to the journal.